Cable communications technology - Bartlett, Eugene R. (McGraw-Hill, 2005)
Cable is now as much in the broadband business as it is television. This book explains the fundamentals of coaxial cable technology and the DSP that controls it, along with the cable modem and voice over IP technology now drastically changing the cable operators’ business. Aimed at working engineers and technicians, it can also be used a textbook for the a basic cable communications course in a 2 year tech program.